Answer:
![y = x \ln 2 +\left(\ln 2 \right)^2-2 \ln 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/5xdgjehd4cjb45n16boh20749uzmgoknzl.png)
Explanation:
Differentiation is an algebraic process that finds the gradient of a curve.
At a point, the gradient of a curve is the same as the gradient of the tangent line to the curve at that point.
![\boxed{\begin{minipage}{5.4 cm}\underline{Chain Rule for Differentiation}\\\\If $y=f(u)$ and $u=g(x)$ then:\\\\$\frac{\text{d}y}{\text{d}x}=\frac{\text{d}y}{\text{d}u}*\frac{\text{d}u}{\text{d}x}$\\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/hhnsgjmxj7dg44oh7yf3ildb5igtgw1gtu.png)
![\boxed{\begin{minipage}{4.5 cm}\underline{Differentiating $x^n$}\\\\If $y=x^n$, then $\frac{\text{d}y}{\text{d}x}=nx^(n-1)$\\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/bqh3zf3rb697porudw91fc15tvw3muj220.png)
![\boxed{\begin{minipage}{4.5 cm}\underline{Differentiating $\ln x$}\\\\If $y=\ln x$, then $\frac{\text{d}y}{\text{d}x}=(1)/(x)$\\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/w0gpga5cr6vab23ursoogt1sez6rqq33qa.png)
Differentiate the given function using the chain rule:
![\begin{aligned}f(x) & = \left(\ln x\right)^2\\\implies f'(x)& = 2\left(\ln x\right)^(2-1) \cdot \frac{\text{d}}{\text{d}x} \ln x\\& = 2\left(\ln x\right)^(1) \cdot (1)/(x)\\& = (2)/(x) \ln x \end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sxen40heqgjicj6cufkjtihzvzasd8g80j.png)
To find the gradient of the function at x = 2, substitute x = 2 into the differentiated function:
![\implies f'(2) = (2)/(2) \ln 2 = \ln 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/xeu3ams71er5xx6vtw41vq25x5ld9zg0hq.png)
Therefore, the gradient of the function at x = 2 is ln(2).
Substitute x = 2 into the function to find the y-value of the point on the curve when x = 2:
![\implies f(2)= \left( \ln 2\right)^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/314xi44zk80o7my7190ath7u5qqhjzngva.png)
Slope-intercept form of a linear equation:
![y=mx+b](https://img.qammunity.org/2023/formulas/mathematics/high-school/smsb8cbft03lwblmi49nf2l6jby2ofxzws.png)
where:
- m is the slope.
- b is the y-intercept.
Substitute the point (2, (ln 2)²) and the found gradient into the slope-intercept formula and solve for b:
![\begin{aligned} y & = mx+b\\\implies \left(\ln 2 \right)^2 & = \ln 2 \cdot 2 + b\\\left(\ln 2 \right)^2 & =2\ln 2 +b\\b & = \left(\ln 2 \right)^2-2 \ln 2\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/k0t2w95qdknl6vfzt4wjy9kf1tditx9hlp.png)
Therefore, the tangent has the equation:
![y = x \ln 2 +\left(\ln 2 \right)^2-2 \ln 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/5xdgjehd4cjb45n16boh20749uzmgoknzl.png)